Визуализация как информационная система поддержки принятия решений на примерах проектирования и производства поршней - Максимова, М. А.; Чигрин, А. В.; Белогуб, Александр Витальевич (НТУ "ХПИ", 2008)
Розглядаються питання візуалізації при проектуванні поршнів і вузлів ДВС, основні тенденції візуалізації поршнів і процесів, що відбуваються при роботі ДВС, основні програмні засоби здобуття статичних і динамічних зображень, подальше вживання отриманого візуального матеріалу. Проведений аналіз різних підходів до процесів візуалізації різних технічних рішень на різних етапах проектування і виробництва поршнів і вузлів ДВС, описані деякі технічні і програмні рішення, що дозволяють істотно скоротити як час здобуття візуального матеріалу, так і час проектування виробу.

The questions of visualization at constructing of pistons and knots of combustion engines are examined, basic tendencies of visualization of pistons and processes, what be going on during work of combustion engines, fixed programmatic assets of receipt of static and dynamic images, further application of the got visual material. The analysis of the different going is conducted near the processes of visualization of different technical decisions on the different stages of planning and production of pistons and knots of combustion engines, some technical and programmatic decisions, allowing substantially to shorten both time of receipt of visual material and time of planning of good, are described.
Keywords: 3D-графика; рендеринг изображения; плагины; утилиты; управляющие файлы; скрипты